Effect of multiple adhesive coating on microshear bond strength to primary tooth dentin. - Beheshteh Malekafzali; Amir Ghasemi; Hassan Torabzadeh; Reza Hamedani; Nekoo Tadayon (Tehran University of Medical Sciences, 2013)
Multiple adhesive coating is a controversial topic, especially in primary dentition that should be clarified. We evaluated the effect of multiple consecutive adhesive resin coatings on the microshear bond strength (μSBS) of composite resin to primary tooth dentin utilizing a filled (Adper Single Bond Plus) and an unfilled (Adper Single Bond) adhesive resin.Thirty extracted primary canines were randomly allocated into two groups based on the adhesive used. Dentin occlusal surfaces were exposed and further polished on 400, 600 and 800-grit silicon-carbide paper. The surfaces were divided into two halves in the labial-lingual orientation. After etching, the adhesives were used either in double coats, or four coats on the halves of the same tooth followed by air evaporation for each layer and finally light curing. Cylinders of composite were bonded to the dentin surfaces. After 24 h shear bond testing was evaluated by Bisco tensile tester. ANOVA, Student t test and paired t test were used for statistical analysis.The mean (standard deviation) for double coats or four coats in single bond were 31.99 (2.94) and 30.25 (2.69), while they were 29.18 (3.35) and 31.26 (2.07) in single bond plus, respectively. No significant differences were found between the double coated specimens and those receiving four coatings with both adhesives (p>0.05). Micro SBS values of Single Bond double coated specimens were significantly higher than Single Bond Plus (p=0.02). In four-coated specimens, there were no significant differences between Single Bond and Single Bond Plus (p=0.26).Applying four coats of adhesive did not improve the μSBS to primary tooth dentin.